Determination of Erosion Hazard Level And Bio-Mechanical Conservation In Post Merapi Eruption Land At Srumbung Magelang - Wardoyo, S Setyo; Purnomo, H; Santosa, AZ Purwono Budi; Priyanto, Sugeng; Anshori, Muhktar (Universitas Muhammadiyah Surakarta, 2014)
The purpose of this study was to determine the Erosion hazard, to look for conservation of bio - mechanical techniques are appropriate . Research methods with overlies topographic maps, soil maps, land use maps, to obtain a Land Unit Map. Determined soil physical properties (texture, structure, permeability) and chemical properties of soil (soil organic matter), slope, slope length, broad of land unit, crops factor and value conservation factors that have been there for Land Unit. Each land unit is determined the amount of land erosion and erosion hazard level. Erosion hazard level is determined based on soil erosion, and soil depth. Erosion hazzard level is used to determine the bio-mechanical conservation, according Hardjowigeno and Sukmana (1995). The results showed that the highest erosion hazard level with an area of 12.947 ha is classified weight (Land unit 15A), and the classification of an area of 14.665 ha is clssified moderately (Land unit 6A). Soil conservation is done in areas with highest erosion hazard level by making individual terraces and âkerandangâ planted as a cover crops.